2016
DOI: 10.1093/gerona/glv210
|View full text |Cite
|
Sign up to set email alerts
|

Improved Function With Enhanced Protein Intake per Meal: A Pilot Study of Weight Reduction in Frail, Obese Older Adults

Abstract: Background:Obesity is a significant cause of functional limitations in older adults; yet, concerns that weight reduction could diminish muscle along with fat mass have impeded progress toward an intervention. Meal-based enhancement of protein intake could protect function and/or lean mass but has not been studied during geriatric obesity reduction.Methods:In this 6-month randomized controlled trial, 67 obese (body mass index ≥30kg/m2) older (≥60 years) adults with a Short Physical Performance Battery score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…None of the participants endorsed suicidal thoughts or behaviors during the study. As reported previously, there was significant weight loss (mean = −8.4 kg) and physiologically-important improvements in SPPB scores at the 6-month end point for both groups, with a significantly greater improvement in the SPPB score for the Protein group (+2.4 points) relative to Control group (+0.9 point) (22). …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…None of the participants endorsed suicidal thoughts or behaviors during the study. As reported previously, there was significant weight loss (mean = −8.4 kg) and physiologically-important improvements in SPPB scores at the 6-month end point for both groups, with a significantly greater improvement in the SPPB score for the Protein group (+2.4 points) relative to Control group (+0.9 point) (22). …”
Section: Resultssupporting
confidence: 71%
“…The results by group have already been reported for primary outcomes of interest, namely, changes in physical function and lean body mass (22). Given minimal group differences for QOL and mental health variables, the absence of a protein-specific hypothesis, and in order to increase power, the two groups were combined for the current analyses.…”
Section: Methodsmentioning
confidence: 83%
“…Many other studies utilized a balanced hypocaloric diet with normal foods, obtaining a 500 to 750 kCal energy deficit per day. This yielded weight losses of between 5% and 10% over 6 to 18 months . The addition of exercise to a hypocaloric diet did not yield significantly greater weight losses than a hypocaloric diet alone .…”
Section: Resultsmentioning
confidence: 94%
“…Studies comparing diet plus exercise, diet alone, and exercise alone revealed improved self‐reported or objective physical function in the diet plus exercise groups, followed by exercise, diet then control. A single study comparing weight loss with diet and exercise with differing protein intakes revealed improved physical function in the higher protein intake (1.2 g/kg/d versus 0.8 g/kg/d) group …”
Section: Resultsmentioning
confidence: 99%
“…However, for the obese, frail, older adult, physical activity must be performed “as tolerated” and is unlikely to provide this protection; the best approach for managing obesity in these individuals remains to be elucidated. New evidence indicating the anabolic advantage of enhancing protein intakes (with or without resistance training) as a means of preserving lean muscle mass and improving physical function during weight reduction may hold promise for this population [ 28 , 29 ].…”
Section: Overview Of the Obesity Challenge In High-risk Populationmentioning
confidence: 99%